Optimisation of construction parameters of gyroscope system on elastic suspension - Koruba, Zbigniew (Computer Assisted Methods in Engineering and Science, 2023)
In the paper are derived the equations of motion of a gyroscope on elastic suspension, mounted on a movable base. An algorithm for the selection of the optimum construction parameters and the matrices of amplifications of the gyroscope regulator is presented. The latter is aimed at the quickest transitory process damping and also at the minimisation of errors resulting from the friction in frame bearings, base angular motion and non-linearity of the impact.